2017
DOI: 10.1016/j.preteyeres.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The connective tissue phenotype of glaucomatous cupping in the monkey eye - Clinical and research implications

Abstract: In a series of previous publications we have proposed a framework for conceptualizing the optic nerve head (ONH) as a biomechanical structure. That framework proposes important roles for intraocular pressure (IOP), IOP-related stress and strain, cerebrospinal fluid pressure (CSFp), systemic and ocular determinants of blood flow, inflammation, auto-immunity, genetics, and other non-IOP related risk factors in the physiology of ONH aging and the pathophysiology of glaucomatous damage to the ONH. The present repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 219 publications
1
49
0
2
Order By: Relevance
“…Yang et al 16 proposed a framework for the pathophysiology of glaucomatous ONH damage. They proposed that optic nerve ‘cupping’ in a monkey study has two main components common to all optic neuropathies: prelaminar thinning and laminar deformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al 16 proposed a framework for the pathophysiology of glaucomatous ONH damage. They proposed that optic nerve ‘cupping’ in a monkey study has two main components common to all optic neuropathies: prelaminar thinning and laminar deformation.…”
Section: Discussionmentioning
confidence: 99%
“…The second component of ‘cupping’ is laminar deformation or laminar cupping, which results from permanent, IOP-induced deformation of the LC and peripapillary scleral connective tissues following ONH connective tissue damage and deformation 16. Burgoyne19 showed that the laminar component of cupping predominates in glaucomatous optic neuropathy and is characterised by progressive posterior displacement of the surface of the ONH.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to recognize that also glaucoma affects non‐neural tissues also (Yang et al. , , ) and that while the inclusion of these components may result in a less than perfect alignment with functional loss, it does not mean that diagnostic accuracy for glaucoma is adversely affected.…”
Section: Discussionmentioning
confidence: 99%
“…Current technology does not allow subtraction of all non-neural components from the width, area or volume measurements currently in use; however, accounting for blood vessels, suggested by some authors (Knighton et al 2012;Patel et al 2014;Ye et al 2016) and adjusting rim measurements accordingly for the PRL, could help in this regard. However, it is important to recognize that also glaucoma affects non-neural tissues also (Yang et al , 2015(Yang et al , 2017 and that while the inclusion of these components may result in a less than perfect alignment with functional loss, it does not mean that diagnostic accuracy for glaucoma is adversely affected.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that IOP‐related stresses may induce extracellular matrix remodelling and chronic changes to the ONH that results in the typical excavated or cupped appearance of a glaucomatous optic disc, which is for the most part irreversible even after the reduction of IOP. Through experimental glaucoma models in monkeys, it has been established that early glaucomatous changes to the ONH include posterior bowing of the lamina and peripapillary sclera that is accompanied by scleral canal expansion, thickening of the LC, and outward migration of the laminar insertion from the sclera into the pia mater .…”
Section: The Lamina Cribrosa As a Biomechanical Structurementioning
confidence: 99%